186k views
2 votes
Help algebra 2 please

Help algebra 2 please-example-1

2 Answers

7 votes

Answer:

x^4 - x^2 - 2x - 1

Explanation:

(x^2+x+1)(x^2-x-1) = x^4 - x^3 - x^2 + x^3 - x^2 - x + x^2 - x - 1

= x^4 - x^2 - 2x - 1

User CatBusStop
by
5.2k points
3 votes

Answer:

option 4

Explanation:

(f*g)(x) =(x² + x+ 1)*(x² - x -1)

= x²*(x² - x -1) + x(x² - x -1) + 1*( x² - x -1)

= x²*x² - x²*x -x²*1 + x*x² - x*x -x*1 + x² - x -1

= x⁴ - x³ - x² +x³ - x² - x + x² - x -1

= x⁴ - x³ + x³ - x² - x² + x² - x - x - 1

= x⁴ - x² - 2x - 1

User Mustafa Candan
by
5.3k points